Synthesis of ZnS-Kaolin as an application of photoreduction of CO2 - Nor Shafiza, Ghazali (2012)
Nowadays,due to the industrialization or urban process cause the high concentration of carbon dioxide(CO2)in environment.CO2 is a trace gases and is the largest factors contribute to the world’s greenhouse gas emissions.Early studies have shown that conventional treatment such as energy conservation,carbon capture and storage and using CO2 as a raw material in a chemical process is efficient method but it have some drawbacks. Advanced oxidation technologies (AOTs) are innovative methods for pollutant treatment and are extremely useful in the case of substances resistant to conventional technologies.In this study,the oxidation process using heterogeneous catalyst assisted with UV light will be used to reduce the concentration of CO2 in environment. Heterogeneous catalyst was prepared using Zinc Sulfide (ZnS) deposited on kaolin as an inert support for catalyst. ZnS-Kaolin catalyst was prepared by using two methods which are by impregnation and hydrothermal method. The results of these two methods was compared and investigated to know which catalyst will be giving a high performance in photo-reduction process.To investigate the performance of the catalyst,ZnS-Kaolin catalyst was characterized by using Brunauer-Emmett-Tellar (BET) method, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM)and X-Ray diffraction (XRD) to study the surface morphology and the characteristics of the catalyst.